Kinetic Analysis of Gluconacetobacter diazotrophicus Cultivated on a Bench Scale: Modeling the Effect of pH and Design of a Sucrose-Based Medium - Gloria M. Restrepo; Alejandro Rincón; Óscar J. Sánchez (Fermentation, 2023)
Gluconacetobacter diazotrophicus is an endophytic bacterium that has shown important plant growth-promoting properties. During the growth of G. diazotrophicus with high carbon source concentrations, organic acids are produced, and pH decreases, thus inhibiting biomass growth. The objective of this work was to design a sucrose-based medium and perform a kinetic analysis of the batch submerged cultivation of this bacterium in a 3 L stirred-tank bioreactor without pH control. A mathematical model was proposed for representing G. diazotrophicus concentration, considering the inhibitory effect of hydrogen ion concentration. It comprises a biomass growth model, a specific growth rate expression that accounts for the inhibitory effect of hydrogen concentration, and a hydrogen model that represents the relationship between hydrogen and biomass concentrations. The sucrose-based medium proved its suitability for G. diazotrophicus growth. A higher biomass concentration (1.10 g/L) was obtained in a modified LGI-P medium containing 30 g/L sucrose with a three-fold increase in biomass production relative to the initial inoculation. The model allowed a satisfactory description of the experimental data obtained, and it could be used to design a cultivation strategy to maximize biomass production leading to the production of an alternative microbial inoculant for plant growth promotion of economically important crops.